An overview of mechanized cotton harvesting : Introduction of AI enabled robot and its implication in mechanization - Suwathiga, M; Surendrakumar, A; Kavitha, R; Raja, R; Kannan, B; Somasundaram, S (Plant Science Today, 2025)
Cotton has been a pivotal crop throughout India's history, maintaining its significant social and economic importance in contemporary Indian society. In India, cotton is harvested manually using traditional hand-picking techniques. However, manual cotton-picking poses drawbacks such as high labor cost, labor shortage and risks to worker’s health due to prolonged exposure to pesticides and repetitive motion injuries, thereby affecting overall productivity and sustainability in the cotton industry. Mechanical harvesting employs advanced machinery to efficiently harvest cotton, reducing its dependence on manual labor and thereby boosting productivity in the fields. Mechanical cottonpicking presents challenges such as high initial investment costs for machinery, potential damage to crops, soil compaction and the need for skilled operators, limiting its widespread adoption in small land holdings. The integration of robotics, automation and precision agriculture has transformed cotton harvesting technology, replacing traditional methods. These innovations improve efficiency and productivity while supporting sustainability by minimizing environmental impact and ensuring continued success of cotton production. Further research and development in artificial intelligence, machine learning and sensor technology are expected to drive continued innovation, making cotton harvesting even more efficient, sustainable and cost-effective for farmers worldwide.